A simulation framework for testing collaborative P2P/ISP traffic engineering mechanisms - Sousa, Pedro (2014)
P2P applications are nowadays commonly used in the Internet for the development of distinct services. As consequence, Internet Service Providers (ISPs) are fac- ing some coexistence problems with P2P applications due to the unpredictable dynamics of such applications, causing traffic to traverse the network links in an unfore- seeable way. As a contribution to this research area, this work presents a simulation framework of a collaborative BitTorrent-like system allowing that enhanced configu- rations can be programmed at the P2P tracker. The developed simulation framework can be used to study, devise and test novel Traffic Engineering (TE) mecha- nisms defined within the ISP vs P2P collaboration area.